Questions for In-Depth Reflection and Improvement of Music Teaching (Appendix to Chapters 1−9) - Kovačič, Bojan (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter presents a series of questions based on the nine chapters of the monograph (Chapters 1–9): How to Introduce Jazz to Children, Voice Hygiene, Music and the Emotional Development of Children, The Influence of Music on Language Development, The Development of Musical Taste in Children, Music and Inclusion: Adapting Lessons for All Pupils, Music Education and Cultural Diversity, Parental Involvement in Music Education, and Ethical Aspects of Music Teaching. The questions are divided into four areas (lesson planning, lesson delivery, observation and evaluation, improvement and development) and enable teachers and students to reflect more closely on their own teaching practise.